Labor Turnover, Wage Structures, and Moral Hazard: The Inefficiency of Competitive Markets - Arnott, Richard J.; Stiglitz, Joseph E. (Journal of Labor Economics, 1985)
A multiperiod, general equilibrium model of the labor market is developed in which risk-averse workers are faced with job-related uncertainty and labor turnover is costly. If a worker is unlucky and suffers a bad job match, he quits and joins another firm, hoping that he will like its work environment more. Because the quality of a job match is unobservable, workers cannot insure against the risk of a bad match. The firm provides implicit insurance against job dissatisfaction, typically by paying workers more than their net marginal products in their early years with the firm and less subsequently. Since the probabilities of the insured-against events (the quit rates over time) are affected by the amount of such insurance provided, this implicit insurance is characterized by moral hazard. Individuals quit when in the absence of insurance they would not. The equilibrium contract balances out efficiency in risk bearing with efficiency in turnover incentives. We show that the equilibrium contract is not (constrained) efficient and indicate why.